Controlled modification of resonant tunneling in metal-insulator-insulator-metal structures - Mitrovic, I. Z.; Weerakkody, A. D.; Sedghi, N.; Ralph, J. F.; Hall, S; Dhanak, V. R.; Luo, Zhenhua; Beeby, S (American Institute of Physics (AIP), 2018)
We present comprehensive experimental and theoretical work on tunnel-barrier rectifiers comprising bilayer (Nb2O5/Al2O3) insulator configurations with similar (Nb/Nb) and dissimilar (Nb/Ag) metal electrodes. The electron affinity, valence band offset, and metal work function were ascertained by X-ray photoelectron spectroscopy, variable angle spectroscopic ellipsometry, and electrical measurements on fabricated reference structures. The experimental band line-up parameters were fed into a theoretical model to predict available bound states in the Nb2O5/Al2O3 quantum well and generate tunneling probability and transmittance curves under applied bias. The onset of strong resonance in the sub-V regime was found to be controlled by a work function difference of Nb/Ag electrodes in agreement with the experimental band alignment and theoretical model. A superior low-bias asymmetry of 35 at 0.1 V and a responsivity of 5 A/W at 0.25 V were observed for the Nb/4 nm Nb2O5/1 nm Al2O3/Ag structure, sufficient to achieve a rectification of over 90% of the input alternate current terahertz signal in a rectenna device.
Keywords: Resonant tunneling; Tunneling; Work functions; Quantum wells; Electronic devices